2021
DOI: 10.3390/mi12101190
|View full text |Cite
|
Sign up to set email alerts
|

The Improvement in Hydrogen Storage Performance of MgH2 Enabled by Multilayer Ti3C2

Abstract: MgH2 has become a hot spot in the research of hydrogen storage materials, due to its high theoretical hydrogen storage capacity. However, the poor kinetics and thermodynamic properties of hydrogen absorption and desorption seriously hinder the development of this material. Ti-based materials can lead to good effects in terms of reducing the temperature of MgH2 in hydrogen absorption and desorption. MXene is a novel two-dimensional transition metal carbide or carbonitride similar in structure to graphene. Ti3C2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 61 publications
(66 reference statements)
1
19
0
Order By: Relevance
“…According to the results of a hydrogen release study from magnesium hydride, after 11 h in the chamber, one endothermic peak is observed, which corresponds to the release of hydrogen from the material. The beginning of hydrogen desorption from MgH 2 was observed at a temperature of 345 • C, and the peak temperature was about 380 • C. These results correlate with the data obtained in other works for milled magnesium hydride [46][47][48][49]. insulator transition during hydrogenation to the MgH2 phase [44].…”
Section: Resultssupporting
confidence: 89%
“…According to the results of a hydrogen release study from magnesium hydride, after 11 h in the chamber, one endothermic peak is observed, which corresponds to the release of hydrogen from the material. The beginning of hydrogen desorption from MgH 2 was observed at a temperature of 345 • C, and the peak temperature was about 380 • C. These results correlate with the data obtained in other works for milled magnesium hydride [46][47][48][49]. insulator transition during hydrogenation to the MgH2 phase [44].…”
Section: Resultssupporting
confidence: 89%
“…Ongoing recent trends in developing novel systems for energy storage have incorporated MXene materials with a 2D structure, as promising hydride hosts [94,156,[176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191][192][193][194]. While only few examples are currently available, it is foreseeable that MXenes will grow to become a mainstream storage matrix for nanoconfined hydride-based materials (Table 7).…”
Section: Mxenementioning
confidence: 99%
“…Due to its wide availability in nature, low cost, high gravimetric (7.6 wt.%) and volumetric (110 g/L) hydrogen storage capacities, the binary hydride, MgH 2 , is arguably the most studied metal hydride and Mg-based materials have been investigated exhaustively by a variety of research groups (Table 11) [34,43,47,53,55,57,61,65,77,78,80,92,94,95,98,102,103,109,110,115,118,121,122,124,130,134,137,146,147,149,158,[168][169][170]172,177,196,198,201,202,204,205,[208][209][210][211][212]…”
Section: Mghmentioning
confidence: 99%
“…16,33,[49][50][51] However, high-energy ball-milling is one of the most commonly used techniques to reduce the particle size of MgH 2 . 16,50,[52][53][54][55] This approach is significantly less expensive, with a high yield for synthesizing materials in the nano range than other approaches like chemical cold rolling and annealing. 56,57 The yield of materials depends on the milling parameters like milling intensity (rpm), the ball to material ratio, milling time, and the process control agent (medium: liquid or gas).…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques explore the synthesis of catalyzed and uncatalyzed MgH 2 16,33,49‐51 . However, high‐energy ball‐milling is one of the most commonly used techniques to reduce the particle size of MgH 2 16,50,52‐55 . This approach is significantly less expensive, with a high yield for synthesizing materials in the nano range than other approaches like chemical cold rolling and annealing 56,57 .…”
Section: Introductionmentioning
confidence: 99%